Clinical and hygienic assessment of bone mineral density in population of ecologically contrasting territories. - O. E. Loskutov; E. M. Biletska; V. V. Kalinicheva; N. M. Onul; D. A. Sinegubov (Medičnì Perspektivi)
Disorder of the relationship between biotic and abiotic elements against the background of anthropogenic stress on the human body affects the course of bone remodeling. It is bone tissue in the human body that has the greatest cumulative properties with respect to many xenobiotics, lead in particular. The accumulation of lead in the bone leads to the replacement of calcium ions by ions of the abiotic element and causes further changes in the bone structure: inhibition of growth processes, decreased density, the development of osteopenia and osteoporosis. In the article, a comparative hygienic analysis of bone mineral density levels (according to T-score) in industrial (n=68) and control (n=70) areas was conducted. The T-score, calculated at the LI-LIV level obtained by the method of dual-energy X-ray absorptiometry was used and was evaluated according to the recommendations of the WHO. The formation of a homogeneous sample of persons for the study was conducted according to the place of residence, age, sex, absence of diseases and regular intake of drugs leading to a decrease in bone mass. Summarizing the results, it should be noted that the population of Dniprо city has a more negative and significant decrease in the bone mineral density (according to the T-score) compared to the same values of the control areas – 2.15-4.6 times and Ukraine's – 1.39-4.21 times. According to WHO recommendations, T-score indices for residents of industrial territory indicate to the presence of osteopenia, while among residents of the control area, the norm for this indicator is noted. Consequently, there is an effect of man-made including lead, pollution of the environment on the level of bone mineral density in the industrial city this contributes to the development of osteoporotic changes in the population.